Digital Transformation and Culinary MSME Peformance: The Mediation Role of Competitive Advantage - Peter, Ruben; Utama, Louis (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
This study aims to analyze the influence of digital transformation on the performance of culinary MSMEs in West Jakarta and to examine the role of competitive advantage as a mediating variable. The research background highlights the increasing adoption of digital technology among MSMEs, although not all business owners experience optimal performance improvements. The study is grounded in the Resource-Based View (RBV) theory, which emphasizes that sustainable competitive advantage can be achieved through the effective utilization of valuable resources such as digital technology. A quantitative approach was applied using a cross- sectional survey design. Data were collected through questionnaires distributed to 160 culinary MSME owners who have implemented digital technologies. The data were analyzed using Partial Least Squares– Structural Equation Modelling (PLS-SEM). The results indicate that digital transformation has a positive and significant effect on MSME performance. Digital transformation also enhances competitive advantage, thereby positively impacting business performance. Moreover, competitive advantage plays a significant mediating role in the relationship between digital transformation and business performance. These findings underscore that the adoption of digital technology must be accompanied by strategies that create added value and differentiation in order to achieve optimal performance outcomes. In practice, this research provides recommendations for MSMEs to strengthen digital competencies and product differentiation, and encourages policymakers to expand digital assistance programs to support MSME development.